2008
DOI: 10.1002/ajmg.b.30740
|View full text |Cite
|
Sign up to set email alerts
|

Genetic influences on the broad spectrum of autism: Study of proband‐ascertained twins

Abstract: An investigation of genetic structures underlying autistic traits was performed with samples from twins for which at least one proband had been ascertained as having autism spectrum disorders (ASDs) in our catchment area. In order to adjust for recent concepts of autism, we employed criteria for the broad spectrum of disease and the childhood autism rating scale (CARS) for quantitative assessment. The CARS test was performed on 45 twin pairs (19 monozygotic, 26 dizygotic) detected with a regional routine scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 47 publications
(47 reference statements)
5
66
0
4
Order By: Relevance
“…The details of the sample population have been described elsewhere. 9,17 A consensus diagnosis of ASDs, based on the DSM-IV criteria, was made on the basis of all the information available in a semi-structured case vignette that was prepared based on medical examination, psychological assessment and a clinical report, through repeated observation, both by psychologists and by pediatric psychiatrists, of children between the ages of 4 and 6 years. Inter-rater reliability was assessed by studying 27 individuals, with their names, ages and zygosity information removed, and the kappa coefficient between the two raters (HT and MT) was 0.70 for AD, AsD, PDDNOS and non-PDD.…”
Section: Methods Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The details of the sample population have been described elsewhere. 9,17 A consensus diagnosis of ASDs, based on the DSM-IV criteria, was made on the basis of all the information available in a semi-structured case vignette that was prepared based on medical examination, psychological assessment and a clinical report, through repeated observation, both by psychologists and by pediatric psychiatrists, of children between the ages of 4 and 6 years. Inter-rater reliability was assessed by studying 27 individuals, with their names, ages and zygosity information removed, and the kappa coefficient between the two raters (HT and MT) was 0.70 for AD, AsD, PDDNOS and non-PDD.…”
Section: Methods Subjectsmentioning
confidence: 99%
“…5,6 There is evidence that autistic traits are highly heritable and are influenced by additive genetic and individual-specific environmental factors both in the general population 7 and in the ASD population. 8,9 In addition, there is evidence that IQ is fairly heritable and is influenced by additive genetic, shared environmental and individualspecific environmental factors both in the general population 10 and in the mild MR population. 11 However, the causal relationship between autistic traits and IQ remains controversial as some family studies of ASDs using standardized IQ tests found a higher rate of cognitive disabilities among siblings but others could not confirm this finding.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Thus, from a genetic point of view, we can interpret families with the highest risk, close to 50%, as transmitting ASDs in a dominant pattern. The risk estimates for our sample under the model, which constrained the highest risk to 0.5 are shown in Figure 1.…”
Section: Major Contribution Of Dominant Inheritance To Asds T Nishiyamentioning
confidence: 99%
“…There is evidence that ASDs are highly heritable, [1][2][3] although ASDs show wide clinical variability and a heterogeneous genetic architecture. 4,5 Dizygotic and sibling concordance rates are about one-tenth of monozygotic concordance rates, suggesting that ASDs are attributable to complex multigenic interactions rather than to a single susceptibility gene.…”
Section: Introductionmentioning
confidence: 99%
“…They are estimated to affect 1 in 68 to 256 children in developed countries, with a male to female ratio of 5:1 (Developmental Disabilities Monitoring Network Surveillance Year 2010 Principal Investigators and Centers for Disease Control and Prevention (CDC) 2014; Taylor et al 2013). They are among the most inheritable neurodevelopmental disorders, with concordance rates of 60% between monozygotic twin pairs for classic autism, that increase to 90% when considering the broader autistic phenotype (BAP; Bailey et al 1995;Folstein and Rutter 1977;Lichtenstein et al 2010;Ritvo et al 1985;Ronald and Hoekstra 2011;Rosenberg et al 2009;Steffenburg et al 1989;Taniai et al 2008). ASD are considered complex multifactorial disorders, with both genetic and environmental risk factors.…”
Section: Introductionmentioning
confidence: 99%